Pengaruh Manajemen Kesiswaan dan Motivasi Belajar Siswa Terhadap Prestasi Belajar Siswa di SMA A. Wahid Hasyim Tebuireng Jombang - Agis Triana; Suwandi Suwandi (Journal on Education, 2023)
learning outcomes are the result of learning actvities carried out by students and can change students, the occurrence of the application of good student management and the existence of strong learning motivation greatly influences the learning outcomes of all students. This study aims to determine the effect of student management on student achievement, and to determine of student motivation on student achievement and to determine of student management and student motivation simultaneously on student achievement. The type of research used is ex-post facto researh. The sampling method used purposive sampling using non-probability techniques conducted at SMA A. Wahid Hasyim Tebuireng Jombang. The population in this study were A. Wahid Hasyim Tebuireng Jombang high school students totalling 807 students, taking a sample of 108 students. The data collection technique in this study used a research instrument using a questionnaire and form of a questionnaire, Analysis of the data in this study used multiple regression analysis by testing validity, reliability, prerequisite test and hypothesis testing. The result of the study prove that student management has no partial effect on student achievement at SMA A. Wahid Hasyim Tebuireng Jombang, seen from the value of student management variable t count of 0.079>t table 1.659 with a siginificance value of more than 0.05 (sig. T=0.937>0.05). there is an influence between student learning motivation on student achievement at SMA A. Wahid Hasyim Tebuireng Jombang with t count of 3.7375>t table of 1.659 with a significance level of less than 0.05 (sig. T=0.001<0.05) there is a simultaneous influence between student management and student learning motivation on student achievement at SMA A. Wahid Hasyim Tebuireng Jombang seen from F count>F table value (5,726>3,080) and significant level of 0.04<0.05